Epidemiology, treatment, and performance-based outcomes in american professional baseball players with symptomatic spondylolysis and isthmic spondylolisthesis - Gould, H. P.; Winkelman, R. D.; Tanenbaum, J. E.; Hu, E.; Haines, C. M.; Hsu, W. K.; Kalfas, I. H.; Savage, J. W.; Schickendantz, M. S.; Mroz, T. E. (The American Journal of Sports Medicine, 2020)
Background: Repetitive lumbar hyperextension and rotation during athletic activity affect the structural integrity of the lumbar spine. While many sports have been associated with an increased risk of developing a pars defect, few previous studies have systematically investigated spondylolysis and spondylolisthesis in professional baseball players.